The examination of flesh firmness in different apple varieties - Orosz-Tóth, Mihály; Kincses, Sándorné (Acta Agraria Debreceniensis, 2019)
Of the different physical features of fruits, one important quality feature is flesh hardness. This is an important parameter to be considered when selling fresh apples, for the manufacturing industry and when entering into storage. In our research, we examined 7 apple varieties, in 2016 and 2017, from the establishment of KITE Zrt. in Derecske and the Horticultural Experimentation Site of Pallag (Pallagi Kertészeti Kísérleti Telep). The plantations took place in accordance with intensive apple production. In both years, samples were collected at the time ripening of the given apple variety. Of the examined apple varieties, 5 of them are resistant to scab (Gaia, Isaaq, Modí, Smeralda, Fujion), 1 is not resistant (Golden Reinders) and 1 (Pinova) is moderately susceptible to scab. The scab resistant apple varieties were correlated to the non-resistant Golden Reinders. Flesh firmness was measured with a fruit penetrometer in each of the seven apple varieties. In the first year a two-month storage experiment was carried out, where the flash firmness after harvest, and after one-month and two-month storage was measured. The results were assessed with the help of the IBM SPSS Statistics 20 program. The goal is to compare the apple varieties based on their flesh firmness, in particular with regard to the resistant varieties.The Isaaq 8.81–8.82 N/cm2 , the Modí 9.18–9.59 N/cm2 and the Fujion 8.66–9.13 N/cm2 , all of which are scab resistant apple varieties, showed a significant initial flesh firmness. During storage, the Pinova apple variety flesh firmness changed the most favourably.